Naringenin confers defence against Phytophthora nicotianae through antimicrobial activity and induction of pathogen resistance in tobacco. (12th September 2022) - Sun, Mingming; Li, Lei; Wang, Chengdong; Wang, Luanming; Lu, Di; Shen, Danyu; Wang, Jie; Jiang, Caihong; Cheng, Lirui; Pan, Xuhao; Yang, Aiguo; Wang, Yuanying; et al.
Abstract: Tobacco black shank caused by Phytophthora nicotianae is a serious disease in tobacco cultivation. We found that naringenin is a key factor that causes different sensitivity to P .  nicotianae between resistant and susceptible tobacco. The level of basal flavonoids in resistant tobacco was distinct from that in susceptible tobacco. Of all flavonoids with different content, naringenin showed the best antimicrobial activity against mycelial growth and sporangia production of P .  nicotianae in vitro. However, naringenin showed very low or no antimicrobial activity to other plant pathogens. We found that naringenin induced not only the accumulation of reactive oxygen species, but also the expression of salicylic acid biosynthesis‐related genes. Naringenin induced the expression of the basal pathogen resistance gene PR1 and the SAR8.2 gene that contributes to plant resistance to P. nicotianae . We then interfered with the expression of the chalcone synthase ( NtCHS ) gene, the key gene of the naringenin synthesis pathway, to inhibit naringenin biosynthesis. NtCHS ‐RNAi rendered tobacco highly sensitive to P .  nicotianae, but there was no change in susceptibility to another plant pathogen, Ralstonia solanacearum . Finally, exogenous application of naringenin on susceptible tobacco enhanced resistance to P .  nicotianae and naringenin was very stable in this environment. Our findings revealed that naringenin plays a core role in the defence against P .  nicotianae and expanded the possibilities for the application of plant secondary metabolites in the control of P. nicotianae . Abstract : This study demonstrates that the plant secondary metabolite naringenin specifically inhibits Phytophthora nicotianae .